2016
DOI: 10.9740/mhc.2016.03.75
|View full text |Cite
|
Sign up to set email alerts
|

Review of pharmacologic treatment in cluster A personality disorders

Abstract: Introduction:A personality disorder is a pervasive and enduring pattern of behaviors that impacts an individual's social, occupational, and overall functioning. Specifically, the cluster A personality disorders include paranoid personality disorder, schizoid personality disorder, and schizotypal personality disorder. Patients with cluster A personality disorders tend to be isolative and avoid relationships. The quality of life may also be reduced in these individuals, which provokes the question of how to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
2
2
0
4
Order By: Relevance
“…O TEz é descrita como um padrão de distanciamento das relações sociais e capacidade limitada na expressão de emoções e afetos [26].…”
Section: Caraterísticas Dos Diferentes Tpsunclassified
See 2 more Smart Citations
“…O TEz é descrita como um padrão de distanciamento das relações sociais e capacidade limitada na expressão de emoções e afetos [26].…”
Section: Caraterísticas Dos Diferentes Tpsunclassified
“…Os indivíduos com TPP são considerados "estranhos" e "excêntricos" pelos outros, inexistência de relações de proximidade e com desconfiança pervasiva em relação aos motivos e comportamentos de terceiros em variados contextos [26].…”
Section: Caraterísticas Dos Diferentes Tpsunclassified
See 1 more Smart Citation
“…Cluster A personality disorders (CAPD, including the paranoid, schizoid and schizotypal types) are characterized by "odd and eccentric" behaviors and share some similar clinical symptomatology with schizophrenia [1], but both their pharmaco-and psychotherapeutic treatment effects are far from satisfactory [2][3][4]. Reasons for their poor therapeutic effects are diverse, and one of them is due to insufficient research regarding their pathology.…”
Section: Introductionmentioning
confidence: 99%
“…In clinics, limited evidence has shown that the paranoid personality disorder is marked heavily by suspicious-and hostile-related perceptual-cognitive "positive" symptoms, the schizoid by extreme social isolation stemming from a lack of desire for interpersonal relationships, and the schizotypal by both perceptual-cognitive "positive" deficits and interpersonal problems [2]. In general, CAPD patients display interpersonal mistrust and sensitivity, even those related to doctors and therapists [3,4]. The interpersonal problems as the core symptoms in these patients were reported to be highly correlated with the negative core beliefs about the self and others [6,7], and the perception of dissimilarity of the self with others [6,8].…”
Section: Introductionmentioning
confidence: 99%